Clinical effectiveness and speed of response of electroconvulsive therapy in treatment‐resistant schizophrenia. Issue 7 (1st June 2019) - Chan, Christopher Yi Wen; Abdin, Edimansyah; Seow, Esmond; Subramaniam, Mythily; Liu, Jianlin; Peh, Chao Xu; Tor, Phern Chern
Abstract : Aim: Although electroconvulsive therapy (ECT) has been shown to be efficacious for patients with treatment‐resistant schizophrenia, there has been limited evidence on the rate of response, cognition, and quality‐of‐life outcomes. The primary aims of the present study were thus to examine the effectiveness and speed of response to ECT in a naturalistic retrospective cohort in patients with treatment‐resistant schizophrenia. Methods: We performed a retrospective database analysis. The primary effectiveness outcome was defined as an improvement of ≥40% from pretreatment scores based on the Brief Psychiatric Rating Scale (BPRS) Psychotic Symptom subscale. Data were included for analysis for all patients with a primary DSM‐5 diagnosis of schizophrenia that was treatment‐resistant and who had had an acute course of ECT initiated for the treatment of schizophrenia between 1 July 2016 and 1 December 2016. Results: A total of 50 inpatients were included for analysis. The present study revealed that 50% of patients showed at least a 40% reduction in BPRS Psychotic Symptom subscale scores after completion of ECT and that 16.7% of patients responded after the first three sessions, 39.3% after six sessions, 46.4% after nine sessions, and 50% after 12 sessions. The greatest improvement in BPRS scores was between the third and sixth ECT sessions. BPRS scores, Clinical Global Impression, Montreal Cognitive Assessment, and Global Assessment of Functioning showed significant improvement. There was no significant difference in quality‐of‐life outcomes. Conclusion: Utilizing modern techniques in treatment‐resistant schizophrenia, this study demonstrates the real‐world effectiveness and rate of response of patients receiving ECT.